2007
DOI: 10.1210/jc.2006-2691
|View full text |Cite
|
Sign up to set email alerts
|

The Application of the Combined Corticotropin-Releasing Hormone plus Desmopressin Stimulation during Petrosal Sinus Sampling Is Both Sensitive and Specific in Differentiating Patients with Cushing’s Disease from Patients with the Occult Ectopic Adrenocorticotropin Syndrome

Abstract: Context:Although bilateral inferior petrosal sinus sampling (BI-PSS) with CRH stimulation is the most accurate procedure for the differential diagnosis of ACTH-dependent Cushing's syndrome (CS), 4 -15% of patients with Cushing's disease (CD) fail to demonstrate diagnostic gradients. Preliminary data suggest that a more potent stimulation by the combined administration of CRH plus desmopressin during BIPSS may provide some diagnostic advantage. A crucial issue, however, is whether such an amplified stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 30 publications
0
27
0
2
Order By: Relevance
“…Stimulation with desmopressin and CRH together, performed to amplify corticotrope responses, identified a central/peripheral ACTH gradient in 46 of 47 patients with Cushing's disease. 63 The use of desmopressin however might mandate additional precautions during the sampling procedure, as this agent is a known hemostatic and causes release of von Willebrand factor as well as other factors of the coagulatory cascade in patients with Cushing's disease. 46 In this context, it is worth recalling that IPSS is an invasive maneuver that requires specific expertise to achieve successful bilateral cannulation and accurate and coordinated blood sampling and minimize untoward effects.…”
Section: Evidence On the Use Of Petrosal Sinus Samplingmentioning
confidence: 99%
“…Stimulation with desmopressin and CRH together, performed to amplify corticotrope responses, identified a central/peripheral ACTH gradient in 46 of 47 patients with Cushing's disease. 63 The use of desmopressin however might mandate additional precautions during the sampling procedure, as this agent is a known hemostatic and causes release of von Willebrand factor as well as other factors of the coagulatory cascade in patients with Cushing's disease. 46 In this context, it is worth recalling that IPSS is an invasive maneuver that requires specific expertise to achieve successful bilateral cannulation and accurate and coordinated blood sampling and minimize untoward effects.…”
Section: Evidence On the Use Of Petrosal Sinus Samplingmentioning
confidence: 99%
“…Gradients of sinus (central) to peripheral ACTH are calculated before and after stimulation with CRH. Cushing's disease is diagnosed when the basal gradient is greater than 2, or the gradient after stimulation is greater than 3 [34]. Administration of CRH to stimulate ACTH secretion during sampling is routinely used to elicit diagnostic gradients in Cushing's disease, and to improve the sensitivity of this procedure [34].…”
Section: (4) a Selective Sinus Sampling Testmentioning
confidence: 99%
“…Desmopressin can also be an option for ACTH stimulation during this procedure, improving the accuracy of the differential diagnosis of ACTH-dependent Cushing's syndrome by amplifying the pituitary-peripheral ratio (7). Moreover, recent published data has suggested that the application of a combined stimulation with CRH plus desmopressin is associated with a high sensitivity without losing specificity (8).…”
Section: Discussionmentioning
confidence: 99%